The effect of trust, communication and satisfaction on loyalty of the car insurance customer - SYARIFAH PUTRI WIDIANINGRUM; WIBISONO SOEDIONO (Jurnal Bisnis dan Akuntansi, 2016)
The purpose of this study was to examine the factors that influence loyalty. Those factors are the trust, communication, and satisfaction. The research sample was 100 Garda Oto members in Jakarta selected by purposive sampling method. The result on this research showed that trust, communication, and satisfaction have positive influence to loyalty.